PENILAIAN KEGIATAN GERAKAN NASIONAL REHABILITASI HUTAN DAN LAHAN DI KABUPATEN BEKASI - Lutfiadi, Ridwan; Rahmanto, Muhammad Ikhwan (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2011)
Gerhan is a forest and land rehabilitation activities (RHL) is coordinated by utilizing all the capabilities of government and society in forest and land rehabilitation inthe area of the watershed (DAS) priority. Gerhan aims to achieve environmental improvements in reforestation and land rehabilitation efforts to tackle floods, landslides, droughts in an integrated, transparent and participatory of all parties, both from the government, local governments, communities, businesses, NGOs, farmer groups, and other community elements . The purpose of this activity is carried out to obtain the extent to which the performance of farmer groups as executor in the location of planting crops in the activities of GN-RHL in 2008 in the district of Jakarta.The methods used in conducting the evaluation / assessment / verification in the field consists of four parts, namely through the measurement and direct observation in the field (with sampling). Assessment conducted on the performance of farmer groups, the realization of planting area, the percentage of growing plants, and plant growth.The results showed that of 12 farmers' groups that considered only two groups of farmers who have sufficient performance category with a value of 14,00 and 14,40, while the performance of 10 other farmers only achieve <13,75 or less category. Average realization of planting area is 84,6%. Growing realization of the highest achievable Prosperous Farmers Group's work, which is 102% and the lowest is growing realization of Farmers Group Sentul Jaya, which is 64,6%. The average percentage growth of plants is 79,71%. and the highest attained Mukti Galih Farmers Group, which is 167,27% and Farmers Group Mulya 25,71% True. Average of 64,77% healthy plants, average plant height 98,15 cm, and the average diameter of plants 1023 cm.